Words in Space and Time : A Historical Atlas of Language Politics in Modern Central Europe - Kamusella, Tomasz (Book collections on Project MUSE., 2021)
"With forty-two extensively annotated maps, this atlas offers novel insights into the history and mechanics of how Central Europe's languages have been made, unmade, and deployed for political action. The innovative combination of linguistics, history, and cartography makes a wealth of hard-to-reach knowledge readily available to both specialist and general readers. It combines information on languages, dialects, alphabets, religions, mass violence, or migrations over an extended period of time. The story first focuses on Central Europe's dialect continua, the emergence of states, and the spread of writing technology from the tenth century onward. Most maps concentrate on the last two centuries. The main storyline opens with the emergence of the Western European concept of the nation, in accord with which the ethnolinguistic nation-states of Italy and Germany were founded. In the Central European view, a "proper" nation is none other than the speech community of a single language. The Atlas aspires to help users make the intellectual leap of perceiving languages as products of human history and part of culture. Like states, nations, universities, towns, associations, art, beauty, religions, injustice, or atheism-languages are artefacts invented and shaped by individuals and their groups"--